Strategi Produksi “Bom P 100 Live” Untuk Pemenuhan Kebutuhan Dalam Negeri Guna Mendukung Ketahanan Alat Utama Sistem Senjata (Studi Di PT. Dahana (Persero) Subang, Provinsi Jawa Barat) - Deden Ependi; Agus Prasetya; Armaidy Armawi (Universitas Gadjah Mada, 2019)
ABSTRACTIndependence in the Field of Major Weapons Systems, especially technology in the defense industry, the government through PT. Dahana in collaboration with PT. Sari Bahari Malang, had developed and produced P 100 Live Bombs. The P 100 Live bomb was a type of high explosive fragmented bomb but was not included in the smart bomb group. The presence of the P 100 Live Bomb was expected to strengthened the Sukhoi Air Force Combat Aircraft storefront for meeting domestic needs to supported the durability of the Weapon System Main Tool. At present the bomb had been mass produced but in its production there were still a number of obstacles this research needs. This study aimed to determined the role of PT. Dahana, knew the inhibiting and supporting factors and formulated strategies in the production of Live P 100 Bombs. The study was conducted using descriptive analysis methods that presented data and facts. Alternative strategies were analyzed by SWOT analysis. The results of the study showed that First, the role of PT. Dahana in the production of Live P 100 Bombs as a lead integrator. Second, six prominent aspects were found, namely technology / machine aspects, regulatory aspects, capital aspects, HR aspects, management aspects, and material aspects. The six aspects, which made the inhibiting factors were material aspects, HR, and capital, while those that made the driving factors were the aspects of technology / machinery, regulation, and management. Third, the SWOT analysis described Quadrant IV, namely the consolidation strategy, “optimizing opportunities and minimizing weaknesses”.ABSTRAKKemandirian dibidang Alat Utama Sistem Senjata khususnya teknologi industri pertahanan, pemerintah melalui PT. Dahana yang bekerjasama dengan PT. Sari Bahari Malang, telah mengembangkan dan memproduksi Bom P 100 Live.Bom P 100 Live adalah jenis bom berfragmentasi daya ledak tinggi tetapibukan termasuk kedalam golonganbom pintar.Hadirnya Bom P 100 Live diharapkan dapat memperkuat etalase senjata Pesawat Tempur Sukhoi TNI AU untuk pemenuhan kebutuhan dalam negeri guna mendukung ketahanan Alat Utama Sistem Senjata.Saat ini bom tersebut telah di produksi secara massal namun dalam produksinya masih menjumpai sejumlah kendala hal ini diperlukannya penelitian.Penelitian ini bertujuan mengetahui peran PT. Dahana, mengetahui faktor penghambat dan pendukung serta merumuskan strategi dalam produksi Bom P 100 Live. Penelitian dilakukan dengan menggunakan metode deskriptif analisis yang memaparkan data dan fakta. Strategi alternatif dianalisis dengan analisis SWOT. Hasil penelitian menunjukkan bahwaPertama, peran PT. Dahana dalam produksi Bom P 100 Live sebagai lead integrator. Kedua, ditemukan enam aspek yang menonjol yaituaspek teknologi/mesin, aspekregulasi, aspek modal, aspek SDM, aspek manjemen, dan aspek material. Keenam aspek tersebut, yang menjadikan faktor penghambat yaitu aspek material, SDM, dan modal, sedangkan yang menjadikan faktor pendorong yaitu aspek teknologi/ mesin, regulasi, dan manajemen.Ketiga, analisis SWOT menggambarkan Kuadran IV, yaitu strategi Konsolidasi, “mengoptimalkan peluang dan meminimalkan kelemahan